Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.21037/atm.2018.09.55
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of allogeneic mesenchymal stem cells therapy for knee osteoarthritis in pigs

Abstract: Background: Intraarticular injection of the mesenchymal stem cells (MSCs) has shown to be successful for treating osteoarthritis (OA). Nevertheless, many studies have been focusing on autologous MSCs. The following study investigates the safety and effectiveness of intraarticular injection of allogenic MSCs in a pig OA model. Methods: Superparamagnetic iron oxide (SPIO) nanoparticles were labelled with bone marrow-derived mesenchymal stem cells (BM-MSCs) to allow cells tracking using magnetic resonance imaging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…In the recent years, mesenchymal stem/stromal cell-based therapy (MSCT) has become a promising way in treating OA. Several studies proved the effect of MSCT in cartilage repair in animal models and even clinical studies (de Windt et al, 2017;Hsu et al, 2018;Koh, Kwon, Kim, Choi, & Tak, 2016;Xia et al, 2018). However, concerning the risk of tumourigenicity (Deng, Zhang, Xie, Zhang, & Tang, 2018), genomic stability, and immunogenicity when using viable cells , there is still a long way before popularization of MSCT in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…In the recent years, mesenchymal stem/stromal cell-based therapy (MSCT) has become a promising way in treating OA. Several studies proved the effect of MSCT in cartilage repair in animal models and even clinical studies (de Windt et al, 2017;Hsu et al, 2018;Koh, Kwon, Kim, Choi, & Tak, 2016;Xia et al, 2018). However, concerning the risk of tumourigenicity (Deng, Zhang, Xie, Zhang, & Tang, 2018), genomic stability, and immunogenicity when using viable cells , there is still a long way before popularization of MSCT in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, no consistency has been observed for the provided benefit in the two OA studies reported in pigs (Table 2). In a well-defined OA model, Xia et al (2018b) found no difference in BM-MSC-treated lesions relative to controls. However, it is unclear whether the labelling of the MSCs with magnetic nanoparticles affect their protective functions (Xia et al, 2018b).…”
Section: Preclinical Studies Assessing Msc-based Therapies For Oamentioning
confidence: 73%
“…In a well-defined OA model, Xia et al (2018b) found no difference in BM-MSC-treated lesions relative to controls. However, it is unclear whether the labelling of the MSCs with magnetic nanoparticles affect their protective functions (Xia et al, 2018b). In contrast, Wu et al (2019) observed improved cartilage repair at both macroscopic and histological levels after two pigs were subjected to a complex surgical intervention of cartilage injury followed by transplantation with UC-MSCs in hyaluronic acid.…”
Section: Preclinical Studies Assessing Msc-based Therapies For Oamentioning
confidence: 73%
“…Knee degeneration can also be induced in animals through surgical means, such as iatrogenic anterior cruciate ligament transection [25], meniscectomy [26], osteochondral fragmentation [27], or tibial plateau fracture [28]. Studies have included and ranged from small animal models such as rats and rabbits to large animal models such as sheep, pigs, and dogs [26,[29][30][31][32].…”
Section: Preclinical Data On Stem Cell Therapy For Knee Degenerationmentioning
confidence: 99%